2013
DOI: 10.1002/pd.4215
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and etiologies of fetal megacystis according to the gestational age at diagnosis

Abstract: Lower urinary tract obstruction is the main etiology of megacystis. Megacystis can also be part of more complex malformations. Outcome of megacystis detected in the first trimester is poor. PUV detected in the third trimester had a better overall survival rate than PUV detected in the second trimester.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
40
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 18 publications
6
40
1
1
Order By: Relevance
“…This finding was reported by Bornes et al [10] who reported that an associated congenital abnormality in 32/84 (38.1 %) of their cases.…”
Section: Discussionsupporting
confidence: 73%
“…This finding was reported by Bornes et al [10] who reported that an associated congenital abnormality in 32/84 (38.1 %) of their cases.…”
Section: Discussionsupporting
confidence: 73%
“…Bornes ve ark.nın yaptığı ve 84 fetüsü değerlendirdikleri retrospektif çalışmada, ilk trimesterde megasistis saptanan hiçbir fetüs yaşamamıştır. 8 Bizim olgularda gebelik terminasyon oranı tüm olgular alındığında %48,2, bu fetüslerin intrauterin kayıp oranları ise %13,7 olarak saptandı. İzole megasistis olgularında terminasyon oranı %42,8, intrauterin kayıp oranı ise %19 olarak saptandı.…”
Section: Discussionunclassified
“…Indeed, while in the first trimester, LUTO is mainly due to stenosis or atresia [20,23,26]; in the second or third trimester it (or LUTO?) is mainly due to PUV [8,19,25,27,28]. Another important etiology of LUTO is PBS, characterized by MC always associated with other malformations (urogenital tract and abdominal muscle hypoplasia).…”
Section: Discussionmentioning
confidence: 99%